KATSINOV: A MEASURING TOOL FOR THE LEVEL OF INNOVATION READINESS : ISBN 978-606-95069-1-2 - Wibowo, Susalit Setya (Technium Books, 2024)
The book: KATSINOV: A MEASURING TOOL FOR THE LEVEL OF INNOVATION READINESS ISBN 978-606-95069-1-2 is published in Technium Books.